2018
DOI: 10.1111/1471-0528.15535
|View full text |Cite
|
Sign up to set email alerts
|

Computerised analysis of intrapartum fetal heart rate patterns and adverse outcomes in the INFANT trial

Abstract: Objective To assess if a computerised decision support system reliably identified abnormal fetal heart rate (FHR) patterns in fetuses with adverse neonatal outcomes in the INFANT trial, and whether its use reduced substandard care. Design Prospective cohort study within a randomised controlled trial. Setting Twenty‐four maternity units in the UK and Ireland. Population or sample A total of 46 614 labours between January 6 2010 and August 31 2013 in the INFANT trial. Methods Panel review of intrapartum and neon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 13 publications
(16 reference statements)
1
19
0
1
Order By: Relevance
“…However, the purpose of the INFANT trial was to address the specific hypothesis that some intrapartum care givers are unable to interpret fetal heart rate (FHR) patterns and this hypothesis was not supported by the results. Moreover, abnormal CTG patterns were common in labours with no adverse outcome (73.9% had at least one yellow alert and 10.5% at least one red alert) . Instead, our review suggests that in most cases of avoidable substandard care, insufficient weight was given to the interpretation of FHR abnormality in the context of often multiple coexisting risk factors, for example fetal growth restriction, preterm labour, oxytocin administration, meconium staining of the amniotic fluid, prolonged labour and pyrexia.…”
mentioning
confidence: 81%
“…However, the purpose of the INFANT trial was to address the specific hypothesis that some intrapartum care givers are unable to interpret fetal heart rate (FHR) patterns and this hypothesis was not supported by the results. Moreover, abnormal CTG patterns were common in labours with no adverse outcome (73.9% had at least one yellow alert and 10.5% at least one red alert) . Instead, our review suggests that in most cases of avoidable substandard care, insufficient weight was given to the interpretation of FHR abnormality in the context of often multiple coexisting risk factors, for example fetal growth restriction, preterm labour, oxytocin administration, meconium staining of the amniotic fluid, prolonged labour and pyrexia.…”
mentioning
confidence: 81%
“…A recent paper and the one‐sided BJOG debate unreservedly concluded that ‘computerising intrapartum cardiotocography (CTG) does not improve predictive value’ because the benefits are unproven by statistical significance tests. Remarkably, more than 800 scientists and statisticians have now called for the retiring of the ‘dichotomous’ nature of statistical significance tests, questioning ‘How statistics so often leads the scientists to deny differences that are clear to see or experience?’ This seems particularly relevant to trials on CTG and ancillary technologies .…”
mentioning
confidence: 99%
“…The INFANT trial showed that the computer‐aided analysis was equivalent to visual CTG interpretation, but (crucially) performed by rigorously trained clinicians under ‘trial conditions’ with not only the benefit of the Hawthorne effect but also ‘crossover‐learning’ from the computerised CTG arm. The paper and the debate make no mention that the ‘crossover‐learning’ has been a major criticism/invalidation of the trial results. Hence, it is possible that the computer‐aided CTG could perform uniformly better than median clinical judgment in the absence of Hawthorne effect and in places around the world with less rigorous training or different staffing resources/structures.…”
mentioning
confidence: 99%
See 2 more Smart Citations